The Effect Of Trust Perceptions, Quality Perceptions, Convenience Perceptions, To Buying Interest Msmes In The City Of Madiun (Case Study On Sambal Pecel the City In Madiun) - Heny Sidanti; Hari Purwanto (Universitas muhammadiyah malang, 2023)
This study aims to determine the effect of perceived trust, perceived quality, and perceived convenience on the buying interest of Sambal Pecel in Madiun City. This study uses a non-probability sampling method, which is to determine the sample by determining the characteristics that are in accordance with the research objectives in determining the number of samples. This situation is also known by the buying interest of consumers who have high perceptions of trust, perceived quality, and perceived ease of buying interest as well as other consumers who will show increased buying interest and trust that are more adaptable to products and more able to accept SME pecel chili products in cities. The results of this study are that Perceived Trust, Perceived Quality, PerceivedConvenience on Purchase Intentions have a positive and significant influence on Sambal Pecel MSMEs in Madiun City. The results of this study are that Perceived Trust, Perceived Quality, Perceived Convenience on Purchase Intentions have a positive andsignificant influence on Sambal Pecel MSMEs in Madiun City. This situation is also known by the buying interest of consumers who have high perceptions of trust, perceived quality, and perceived ease of buying interest as well as other consumers who will show increased buying interest and trust that are more adaptable to products and more able to accept SME pecel chili products in cities. The results of this study are that Perceived Trust, Perceived Quality, Perceived Convenience on Purchase Intentions have a positive and significant influence on Sambal Pecel MSMEs in Madiun City and a high perception of ease of purchase intention as well as to other consumers will show increased buying interest and trust that is more adaptable to products and more able to accept SME pecel chili products in Madiun City. Keywords: Trust Perceptions, Quality Perceptions, Convenience Perceptions, Buying Interest